Arrangements of Space Utilization Control in Tourism Areas Based on Justice and Local Wisdom in Realizing Community Welfare - I Gusti Ngurah Muliarta; I Nyoman Putu Budiartha; I Gusti Bagus Suryawan (Warmadewa Press, 2023)
This study delves into the regulation of space utilization control in tourism areas, exploring its nature, legal aspects, and models based on Law No. 6/2023. The main legal queries addressed are the nature of these regulations, their alignment with Ratio Legis, and proposing a model for justice-based control in tourism space. Employing a normative legal research methodology, this study adopts statutory, conceptual, legal historical, philosophical, and comparative legal approaches. Primary, secondary, and non-legal materials are used for analysis. The research concludes that controlling space utilization in tourism areas involves fairness and local wisdom, emphasizing alignment with societal values while addressing governmental, business, and community needs. Ratio Legis under Law No. 6/2023 simplifies licensing to foster employment opportunities and community economic growth, overriding zoning regulations. The proposed control model emphasizes; regulating activities based on space suitability, providing incentives and disincentives, aligning with local wisdom values, and imposing sanctions for compliance. This research contributes insights for just and locally rooted control mechanisms, ensuring community welfare while harnessing the potential of tourism spaces in harmony with societal values and legal regulations.